The effects of DENV serotype competition and co-infection on viral kinetics in Wolbachia-infected and uninfected Aedes aegypti mosquitoes - M. Novelo (Parasites & Vectors, 2021)
Abstract Background The Aedes aegypti mosquito is responsible for the transmission of several medically important arthropod-borne viruses, including multiple serotypes of dengue virus (DENV-1, -2, -3, and -4). Competition within the mosquito between DENV serotypes can affect viral infection dynamics, modulating the transmission potential of the pathogen. Vector control remains the main method for limiting dengue fever. The insect endosymbiont Wolbachia pipientis is currently being trialed in field releases globally as a means of biological control because it reduces virus replication inside the mosquito. It is not clear how co-infection between DENV serotypes in the same mosquito might alter the pathogen-blocking phenotype elicited by Wolbachia in Ae. aegypti. Methods Five- to 7-day-old female Ae. aegypti from two lines, namely, with (wMel) and without Wolbachia infection (WT), were fed virus-laden blood through an artificial membrane with either a mix of DENV-2 and DENV-3 or the same DENV serotypes singly. Mosquitoes were subsequently incubated inside environmental chambers and collected on the following days post-infection: 3, 4, 5, 7, 8, 9, 11, 12, and 13. Midgut, carcass, and salivary glands were collected from each mosquito at each timepoint and individually analyzed to determine the percentage of DENV infection and viral RNA load via RT-qPCR. Results We saw that for WT mosquitoes DENV-3 grew to higher viral RNA loads across multiple tissues when co-infected with DENV-2 than when it was in a mono-infection. Additionally, we saw a strong pathogen-blocking phenotype in wMel mosquitoes independent of co-infection status. Conclusion In this study, we demonstrated that the wMel mosquito line is capable of blocking DENV serotype co-infection in a systemic way across the mosquito body. Moreover, we showed that for WT mosquitoes, serotype co-infection can affect infection frequency in a tissue- and time-specific manner and that both viruses have the potential of being transmitted simultaneously. Our findings suggest that the long-term efficacy of Wolbachia pathogen blocking is not compromised by arthropod-borne virus co-infection. Graphic Abstract